Composite gel electrolyte membrane and preparation method thereof

By using a method of inlined hot press composite inorganic oxide and polymer matrix in solid-state lithium batteries and polymerizing gel electrolytes in situ on it, the problems of insufficient mechanical rigidity of the composite electrolyte membrane and limited application of flame retardant are solved, and a composite gel electrolyte membrane with high conductivity, stability and mechanical strength is achieved, which is suitable for solid-state lithium metal batteries with high energy density.

CN119581655APending Publication Date: 2025-03-07ZHENGZHOU ZHONGKE EMERGING IND TECH RES INST +1

Patent Information

Application Number
CN202411900009.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In solid-state lithium batteries, the existing composite electrolyte membranes are insufficient in mechanical rigidity, flame retardants are limited in high energy density and long cycle applications, and the electrospinning process is complex and practical.

Method used

Under inert gas conditions, the polymer precursor, ionic liquid and composite lithium salt are dissolved in an organic solvent. After stirring and reaction, the inorganic oxide is composited with the polymer matrix by inline hot pressing to form an oxide-based film, and the gel electrolyte precursor solution is polymerized in situ on its surface to prepare a composite gel electrolyte membrane.

Benefits of technology

It improves lithium ion conductivity, electrochemical stability and mechanical elasticity, inhibits the growth and puncture of lithium dendrites, simplifies the battery assembly process, realizes desegmentation, and shows high discharge specific capacity and good cycling performance in high-energy density solid-state lithium metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581655A_ABST
    Figure CN119581655A_ABST
Patent Text Reader

Abstract

The invention provides a composite gel electrolyte membrane and a preparation method thereof, belongs to the technical field of solid-state batteries, and aims to solve the technical problem of low ionic conductivity of solid-state electrolyte. The preparation method of the composite gel electrolyte membrane comprises the following steps: (1) dissolving a polymer precursor, an ionic liquid and a composite lithium salt in an organic solvent to obtain a gel electrolyte precursor solution; (2) dispersing an inorganic oxide on the surface of the polymer matrix, and performing hot-pressing compounding to obtain an oxide-based membrane; and (3) coating the surface of the oxide-based membrane with the gel electrolyte precursor solution, and carrying out curing treatment to obtain the composite gel electrolyte membrane. The composite gel electrolyte membrane provided by the invention is prepared in a simple in-situ polymerization manner, forms an organic / inorganic compact composite membrane, forms dual-ion synergy, has good mechanical elasticity, high ionic conductivity and high flame retardance, and can effectively inhibit the growth and puncture of lithium dendrites in a lithium metal negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state batteries, and in particular relates to a solid-state electrolyte. Background Art

[0002] Solid-state battery technology has become a key common technology for battery companies at home and abroad to develop, and plays an important role in promoting battery technology innovation and industrial development. Solid-state batteries use solid electrolytes to partially or completely replace liquid electrolytes, which can effectively improve the energy density and safety of lithium batteries. However, the high cost, low ionic conductivity, and high solid-solid contact interface resistance of solid electrolytes have restricted the commercialization of solid-state batteries. Gel electrolytes are widely used in the field of solid-state lithium batteries due to their high plasticity, high flexibility and high stability. With the development of practical high-energy-density, long-cycle solid-state batteries by researchers, simple and practical polymerization processes are currently used to prepare organic-inorganic composite gel electrolytes. The experimental methods of this type of electrolyte are simple to operate, easy to control, and have great experimental controllability. The composite gel electrolyte membrane can effectively improve the ionic conductivity of the electrolyte, reduce the interface impedance between the electrolyte and the electrode of the solid-state battery, and improve the cycle stability and energy density of the solid-state battery by virtue of its excellent compatibility.

[0003] For example, patent publication number CN 117747922A discloses a new flame-retardant composite electrolyte, a manufacturing method, and a high-safety flame-retardant lithium battery made of the new flame-retardant composite electrolyte. The flame-retardant composite electrolyte includes a porous organic-inorganic composite membrane and a flame-retardant gel electrolyte. The porous organic-inorganic composite membrane is made by electrospinning an organic-inorganic composite solution precursor and then subjected to a subsequent high-temperature heat treatment or hot pressing treatment. The flame-retardant gel electrolyte is in situ cured / polymerized in the pores of the organic-inorganic composite membrane to form a flame-retardant composite electrolyte. However, the electrolyte membrane prepared based on this process has limited mechanical rigidity, and the flame retardant itself is limited in the application of high energy density and long cycle lithium batteries, and cannot achieve high specific energy positive electrode interface contact stability. At the same time, the electrospinning process is relatively complex to operate and has strict requirements on experimental details, and the prepared electrolyte membrane has low practicality. Summary of the invention

[0004] In view of the above technical problems, the present invention proposes a composite gel electrolyte membrane and a preparation method thereof, which improves the electrochemical properties of gel electrolyte in solid-state lithium metal batteries, so that the lithium ion conductivity, electrochemical stability and mechanical elasticity of the prepared composite gel electrolyte membrane are improved, and the growth and puncture of lithium dendrites during the battery cycle are effectively inhibited. At the same time, the assembly process of the solid-state battery is simplified to achieve the removal of the diaphragm. The prepared composite gel electrolyte membrane can be used in high-energy-density solid-state lithium metal batteries.

[0005] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] A method for preparing a composite gel electrolyte membrane comprises the following steps:

[0007] (1) Under inert gas conditions, a certain mass content of polymer precursor, ionic liquid and composite lithium salt are dissolved in an organic solvent, and stirred for reaction for 0.5 to 36 hours under a certain mechanical strength to obtain a gel electrolyte precursor solution;

[0008] (2) Under inert gas conditions, a certain concentration of inorganic oxide and polymer matrix are dispersed through a high dispersion screen onto the surface of a polymer matrix with a porosity of 5% to 70% and a thickness of 2 to 80 μm, and embedded hot pressing is performed at a pressure of 20 to 500 MPa and a heating temperature of 45 to 200° C. After hot pressing for 0.1 to 6 hours, an oxide-based film is obtained;

[0009] (3) Under inert gas conditions, the gel electrolyte precursor solution of step 1) is coated on the surface of the oxide base film, and in-situ polymerized and cured at 25 to 80° C. for 1 to 160 hours to obtain a composite gel electrolyte membrane.

[0010] The mass ratio of the gel electrolysis precursor solution to the oxide-based film is 1:(0.5-2).

[0011] Furthermore, the polymer precursor in step (1) comprises at least one of 1,3-dioxolane, 1,4-dioxane, propylene oxide, tetrahydrofuran, and dimethyl dioxirane.

[0012] Furthermore, the ionic liquid in step (1) comprises at least one of imidazole ionic liquids, pyridine ionic liquids, pyrrolidine ionic liquids, quaternary amine ionic liquids, piperidine ionic liquids or quaternary phosphonium ionic liquids.

[0013] Furthermore, the composite lithium salt in step (1) includes at least one of lithium trifluoromethylsulfonyl imide, lithium trifluoromethylsulfonyl imide, lithium bis(oxalatoborate), lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium chloride, lithium hexafluorophosphate, lithium difluorooxalatoborate and lithium perchlorate.

[0014] Furthermore, the organic solvent in step (1) is a non-aqueous solvent, including at least one of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl formate, methyl acetate, N,N-dimethylacetamide, fluoroethylene carbonate, dimethyl ether, vinyl sulfite, propylene sulfite, tetrahydrofuran, and hexamethylene diisocyanate.

[0015] Furthermore, the inorganic oxide in step (2) includes at least one of lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium titanium phosphate, lithium germanium aluminum phosphate, and lithium lanthanum titanium oxide.

[0016] Furthermore, in step (2), the polymer matrix is ​​at least one of non-woven fabric, fiber membrane, meltblown fabric, and porous diaphragm.

[0017] Furthermore, the concentration of the polymer precursor is 1-65%, the concentration of the ionic liquid is 0.1-23%, the concentration of the composite lithium salt is 0.2-20%, the concentration of the organic solvent is 2-55%, and the loading amount of the inorganic oxide in the oxide-based film is 0.005-0.1 g / cm 2 . .

[0018] Furthermore, the particle size of the inorganic oxide in step (2) is in the range of 0.2-10 μm.

[0019] Furthermore, the polymer matrix described in step (2) has a porosity of 5%-70% and a thickness of 2-80 μm.

[0020] Furthermore, the coating method of the gel electrolyte precursor solution in step (3) includes at least one of spin coating, dip coating, spray coating, flat blade coating, and cast coating.

[0021] Furthermore, the embedded hot pressing method of the oxide is at least one of single-sided dispersed internal pressure, double-sided dispersed internal pressure, and sandwich structure internal pressure, the pressing size is 20 to 500 MPa, the heating temperature is 45 to 200° C., and the hot pressing time is 0.1 to 6 hours.

[0022] The single-sided dispersion internal pressure is to disperse the inorganic oxide on the surface of the polymer matrix and then hot press composite it; the double-sided dispersion internal pressure is to first disperse the inorganic oxide on the surface of one side of the polymer matrix and then hot press composite it, and then disperse the inorganic oxide on the other side of the polymer matrix and hot press composite it again; the sandwich structure internal pressure is to disperse the inorganic oxide on the surface of the polymer matrix and then cover it with another polymer matrix for hot pressing composite, forming a sandwich structure with upper and lower polymer matrices and inorganic oxide in the middle.

[0023] Furthermore, the oxide base film has a thickness of 10 to 65 μm.

[0024] Furthermore, the composite gel electrolyte membrane has a thickness of 12 to 130 μm.

[0025] Furthermore, the curing treatment of the gel electrolyte membrane includes at least one of in-situ thermal polymerization or in-situ photopolymerization, the polymerization curing temperature is 25 to 80° C., and the curing time is 1 to 160 hours.

[0026] Furthermore, the composite gel electrolyte membrane is used in the field of solid-state lithium metal batteries.

[0027] Beneficial effects of the present invention:

[0028] 1. The present invention prepares an oxide-based film by compounding an inorganic oxide and a polymer matrix through an embedded hot pressing method, which not only improves the stability of the electrolyte-electrode interface contact, but also replaces the original solid-state lithium battery separator to achieve the elimination of the separator;

[0029] 2. The present invention solidifies the gel electrolyte on the oxide-based film by an in-situ polymerization method, thereby improving the mechanical strength of the gel electrolyte film in the battery test of the solid-state lithium metal battery, and the preparation process is simple and the cost is low;

[0030] 3. The oxide-based film prepared by the present invention has high electrical conductivity and high mechanical strength, and can effectively inhibit the growth and puncture of lithium dendrites during the long cycle of lithium batteries;

[0031] 4. The composite gel electrolyte membrane prepared by the present invention is added with ionic liquid, and the oxide-based membrane is added with inorganic oxide. While ensuring the mechanical elasticity of the electrolyte membrane, the inorganic oxide and the ionic liquid form a bicontinuous structure through synergistic action. In addition, the ionic liquid gives the gel electrolyte precursor solution better wettability, and can better infiltrate into the polymer matrix, so that the gel electrolyte membrane has high ionic conductivity, high thermal stability and a wide potential window;

[0032] 5. The composite gel electrolyte membrane prepared by the present invention is applied to solid-state lithium metal batteries. Under room temperature conditions, it exhibits a high ionic conductivity of 0.83×10 -3 S / cm, as well as high discharge specific capacity and good cycle performance. At room temperature, the first discharge specific capacity at 0.5C rate is 169mAh / g, and the first efficiency is 98%. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 This is a schematic diagram of the cross-sectional structure of the composite gel electrolyte membrane in Example 1, wherein 1. gel electrolyte chain; 2. ion liquid channel; 3. gel layer containing organic solvent and composite lithium salt; 4. polymer matrix; 5. inorganic oxide. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] An in-situ polymerized composite gel electrolyte membrane, the structural schematic diagram of which is shown in Figure 1 As shown, in the middle is an oxide-based membrane composed of a polymer matrix 4 and an inorganic oxide 5, and the upper and lower sides of the oxide-based membrane are coated with a gel layer 3 containing an organic solvent and a complex lithium salt. The polymer precursor in the gel layer is polymerized to form a gel electrolyte chain 1, and an ion liquid channel 2 is formed inside.

[0038] The preparation of the composite gel electrolyte membrane includes the following steps:

[0039] Under inert gas conditions, 3.4 g of 1,3-dioxolane, 1.2 g of 1-ethyl-3-methylimidazolium tetrafluoroborate and 0.95 g of lithium trifluoromethylsulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate were dissolved in 1.5 g of fluoroethylene carbonate, wherein the mass ratio of lithium trifluoromethylsulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate was 6:3:1. The reaction was stirred for 2 h under a certain mechanical strength to obtain a gel electrolyte precursor solution; 1.8 g of lithium lanthanum zirconium oxide powder with a particle size of 300 nm was dispersed through a high-dispersion sieve onto the surface of a porous non-woven fabric with a porosity of 35% and a thickness of 7 μm, and the loading per unit area was 0.03 g / cm 2 , and covered with the same porous non-woven fabric again to form a sandwich structure, and embedded hot pressing was performed with a pressure of 300MPa and a heating temperature of 45°C. After hot pressing for 0.5h, an oxide-based membrane was obtained; the prepared gel electrolyte precursor solution was dip-coated on the surface of the oxide-based membrane, and in-situ polymerization was carried out at 25°C for 24h to obtain a composite gel electrolyte membrane with a membrane thickness of 18μm.

[0040] Example 2

[0041] A method for preparing a composite gel electrolyte membrane by in-situ polymerization, comprising the following steps:

[0042] Under inert gas conditions, 3.4 g of 1,3-dioxolane, 1.2 g of N-methyl, propylpiperidinium bis(trifluoromethanesulfonyl imide) salt and 0.95 g of lithium trifluoromethanesulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate were dissolved in 1.5 g of fluoroethylene carbonate, wherein the mass ratio of lithium trifluoromethanesulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate was 6:3:1. The reaction was stirred for 2 h under a certain mechanical strength to obtain a gel electrolyte precursor solution; 1.8 g of lithium germanium aluminum phosphate powder with a particle size of 500 nm was dispersed through a high-dispersion sieve onto the surface of a porous non-woven fabric with a porosity of 35% and a thickness of 7 μm, and the loading per unit area was 0.032 g / cm 2 , and covered with the same porous non-woven fabric again to form a sandwich structure, and embedded hot pressing was performed with a pressure of 300MPa and a heating temperature of 45°C. After hot pressing for 0.5h, an oxide-based membrane was obtained; the prepared gel electrolyte precursor solution was dip-coated on the surface of the oxide-based membrane, and in-situ polymerization was carried out at 25°C for 24h to obtain a composite gel electrolyte membrane with a membrane thickness of 18μm.

[0043] Example 3

[0044] A method for preparing a composite gel electrolyte membrane by in-situ polymerization, comprising the following steps:

[0045] Under inert gas conditions, 3.4 g of 1,3-dioxolane, 1.2 g of N-methyl, propylpiperidinium bis(trifluoromethanesulfonyl imide) salt and 0.95 g of lithium trifluoromethanesulfonyl imide and lithium hexafluorophosphate were dissolved in 1.5 g of fluoroethylene carbonate and hexamethylene diisocyanate, wherein the mass ratio of lithium trifluoromethanesulfonyl imide and lithium hexafluorophosphate was 6:1, and the mass ratio of fluoroethylene carbonate and hexamethylene diisocyanate was 4:1. The reaction was stirred for 2 h under a certain mechanical strength to obtain a gel electrolyte precursor solution; 1.8 g of lithium lanthanum zirconium oxide powder with a particle size of 300 nm was dispersed through a high-dispersion screen onto the surface of a porous diaphragm with a porosity of 50% and a thickness of 7 μm, and the loading per unit area was 0.031 g / cm 2 , and then covered with the same porous diaphragm again to form a sandwich structure, and then embedded hot pressing was performed with a pressure of 300 MPa and a heating temperature of 45°C. After hot pressing for 0.5 h, an oxide-based membrane was obtained; the prepared gel electrolyte precursor solution was dip-coated on the surface of the oxide-based membrane, and in-situ polymerization was carried out at 25°C for 24 h to obtain a composite gel electrolyte membrane with a membrane thickness of 17 μm.

[0046] Example 4

[0047] A method for preparing a composite gel electrolyte membrane by in-situ polymerization, comprising the following steps:

[0048] Under inert gas conditions, 3.4 g of 1,3-dioxolane, 1.2 g of N-methyl, propylpiperidinium bis(trifluoromethanesulfonyl imide) salt and 0.95 g of lithium trifluoromethanesulfonyl imide and lithium hexafluorophosphate were dissolved in 1.5 g of fluoroethylene carbonate, wherein the mass ratio of lithium trifluoromethanesulfonyl imide to lithium hexafluorophosphate was 6:1. The reaction was stirred for 2 h under a certain mechanical strength to obtain a gel electrolyte precursor solution; 1.7 g of lithium lanthanum zirconium oxide powder with a particle size of 300 nm was dispersed through a high-dispersion sieve onto the surface of a porous non-woven fabric with a porosity of 35% and a thickness of 9 μm, and the loading per unit area was 0.031 g / cm 2 , single-side embedded hot pressing was carried out with a pressure of 300 MPa and a heating temperature of 45°C. After hot pressing for 0.5 h, an oxide-based membrane was obtained; the prepared gel electrolyte precursor solution was dip-coated on the surface of the oxide-based membrane, and in-situ polymerization was carried out at 25°C for 24 h to obtain a composite gel electrolyte membrane with a membrane thickness of 16 μm.

[0049] Example 5

[0050] A method for preparing a composite gel electrolyte membrane by in-situ polymerization, comprising the following steps:

[0051] Under inert gas conditions, 3.4 g of 1,3-dioxolane, 1.2 g of 1-ethyl-3-methylimidazolium tetrafluoroborate and 0.95 g of lithium trifluoromethylsulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate were dissolved in 1.5 g of fluoroethylene carbonate, wherein the mass ratio of lithium trifluoromethylsulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate was 6:3:1. The reaction was stirred for 2 h under a certain mechanical strength to obtain a gel electrolyte precursor solution; 1.8 g of lithium lanthanum titanium oxide with a particle size of 500 nm was dispersed through a high-dispersion sieve onto the surface of a porous non-woven fabric with a porosity of 35% and a thickness of 7 μm, and the loading per unit area was 0.034 g / cm 2 , and covered with the same porous non-woven fabric again to form a sandwich structure, and embedded hot pressing was performed with a pressure of 300MPa and a heating temperature of 45°C. After hot pressing for 0.5h, an oxide-based membrane was obtained; the prepared gel electrolysis precursor solution was dip-coated on the surface of the oxide-based membrane, and in-situ polymerization was carried out at 25°C for 24h to obtain a composite gel electrolyte membrane with a membrane thickness of 19μm.

[0052] Example 6

[0053] A method for preparing a composite gel electrolyte membrane by in-situ polymerization, comprising the following steps:

[0054] Under inert gas conditions, 3.4 g of 1,3-dioxolane, 1.2 g of 1-ethyl-3-methylimidazolium tetrafluoroborate and 0.95 g of lithium trifluoromethylsulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate were dissolved in 1.5 g of fluoroethylene carbonate, wherein the mass ratio of lithium trifluoromethylsulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate was 6:3:1. The mixture was stirred for 2 h under a certain mechanical strength to obtain a gel electrolyte precursor solution. 1.8 g of lithium lanthanum zirconium oxide powder with a particle size of 300 nm was dispersed through a high-dispersion sieve onto the surface of a porous non-woven fabric with a porosity of 35% and a thickness of 7 μm, and the loading per unit area was 0.034 g / cm 2 , and embedded hot pressing is performed with a pressure of 300 MPa and a heating temperature of 45°C. After hot pressing for 0.5 h, an oxide-based membrane is obtained; the prepared gel electrolyte precursor solution is dip-coated on the surface of the oxide-based membrane, and in-situ polymerization is carried out at 25°C for 24 h to obtain a composite gel electrolyte membrane with a membrane thickness of 17 μm.

[0055] Example 7

[0056] A method for preparing a composite gel electrolyte membrane by in-situ polymerization, comprising the following steps:

[0057] Under inert gas conditions, 3.4 g of 1,3-dioxolane, 1.2 g of 1-ethyl-3-methylimidazolium tetrafluoroborate and 0.17 g of lithium trifluoromethylsulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate were dissolved in 1.5 g of fluoroethylene carbonate, wherein the mass ratio of lithium trifluoromethylsulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate was 6:3:1. The mixture was stirred for 2 h under a certain mechanical strength to obtain a gel electrolyte precursor solution. 1.8 g of lithium lanthanum zirconium oxide powder with a particle size of 300 nm was dispersed through a high-dispersion sieve onto the surface of a porous non-woven fabric with a porosity of 35% and a thickness of 7 μm, and the loading per unit area was 0.036 g / cm 2 , and covered with the same porous non-woven fabric again to form a sandwich structure, and embedded hot pressing was performed with a pressure of 300MPa and a heating temperature of 45°C. After hot pressing for 0.5h, an oxide-based membrane was obtained; the prepared gel electrolysis precursor solution was dip-coated on the surface of the oxide-based membrane, and in-situ polymerization was carried out at 25°C for 24h to obtain a composite gel electrolyte membrane with a membrane thickness of 19μm.

[0058] Example 8

[0059] A method for preparing a composite gel electrolyte membrane by in-situ polymerization, comprising the following steps:

[0060] Under inert gas conditions, 3.4 g of 1,3-dioxolane, 1.2 g of 1-ethyl-3-methylimidazolium tetrafluoroborate and 0.95 g of lithium trifluoromethylsulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate were dissolved in 1.5 g of fluoroethylene carbonate, wherein the mass ratio of lithium trifluoromethylsulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate was 6:3:1. The mixture was stirred for 2 h under a certain mechanical strength to obtain a gel electrolyte precursor solution. 0.45 g of lithium lanthanum zirconium oxide powder with a particle size of 300 nm was dispersed through a high-dispersion sieve onto the surface of a porous non-woven fabric with a porosity of 35% and a thickness of 7 μm, and the loading per unit area was 0.033 g / cm 2 , and covered with the same porous non-woven fabric again to form a sandwich structure, and embedded hot pressing was performed with a pressure of 300MPa and a heating temperature of 45°C. After hot pressing for 0.5h, an oxide-based membrane was obtained; the prepared gel electrolysis precursor solution was dip-coated on the surface of the oxide-based membrane, and in-situ polymerization was carried out at 25°C for 24h to obtain a composite gel electrolyte membrane with a membrane thickness of 19μm.

[0061] Example 9

[0062] A method for preparing a composite gel electrolyte membrane by in-situ polymerization, comprising the following steps:

[0063] Under inert gas conditions, 3.4 g of 1,3-dioxolane, 0.41 g of 1-ethyl-3-methylimidazolium tetrafluoroborate and 0.95 g of lithium trifluoromethylsulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate were dissolved in 1.5 g of fluoroethylene carbonate, wherein the mass ratio of lithium trifluoromethylsulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate was 6:3:1. The mixture was stirred for 2 h under a certain mechanical strength to obtain a gel electrolyte precursor solution. 1.8 g of lithium lanthanum zirconium oxide powder with a particle size of 300 nm was dispersed through a high-dispersion sieve onto the surface of a porous non-woven fabric with a porosity of 35% and a thickness of 7 μm, and the loading per unit area was 0.032 g / cm 2 , and covered with the same porous non-woven fabric again to form a sandwich structure, and embedded hot pressing was performed with a pressure of 300MPa and a heating temperature of 45°C. After hot pressing for 0.5h, an oxide-based membrane was obtained; the prepared gel electrolyte precursor solution was dip-coated on the surface of the oxide-based membrane, and in-situ polymerization was carried out at 25°C for 24h to obtain a composite gel electrolyte membrane with a membrane thickness of 18μm.

[0064] Example 10

[0065] A method for preparing a composite gel electrolyte membrane by in-situ polymerization, comprising the following steps:

[0066] Under inert gas conditions, 3.4 g of 1,3-dioxolane, 1.2 g of N-methyl, propylpiperidinium bis(trifluoromethanesulfonyl imide) salt and 0.95 g of lithium trifluoromethanesulfonyl imide and lithium hexafluorophosphate were dissolved in 1.5 g of fluoroethylene carbonate, wherein the mass ratio of lithium trifluoromethanesulfonyl imide to lithium hexafluorophosphate was 6:1. The reaction was stirred for 2 h under a certain mechanical strength to obtain a gel electrolyte precursor solution; 1.7 g of lithium lanthanum zirconium oxide powder with a particle size of 300 nm was dispersed through a high-dispersion sieve onto the surface of a porous non-woven fabric with a porosity of 35% and a thickness of 9 μm, and the loading per unit area was 0.031 g / cm 2 , and covered with the same porous non-woven fabric again to form a sandwich structure, and embedded hot pressing was performed with a pressure of 300MPa and a heating temperature of 45°C. After hot pressing for 0.5h, an oxide-based membrane was obtained; the prepared gel electrolyte precursor solution was dip-coated on the surface of the oxide-based membrane, and in-situ polymerization was carried out at 25°C for 24h to obtain a composite gel electrolyte membrane with a membrane thickness of 21μm.

[0067] Comparative Example 1

[0068] Under inert gas conditions, 3.4 g of 1,3-dioxolane and 0.95 g of lithium trifluoromethylsulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate were dissolved in 1.5 g of fluoroethylene carbonate, wherein the mass ratio of lithium trifluoromethylsulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate was 6:3:1. The reaction was stirred for 2 h under a certain mechanical strength to obtain a gel electrolyte precursor solution; 1.8 g of lithium lanthanum zirconium oxide powder with a particle size of 300 nm was dispersed through a high-dispersion sieve onto the surface of a porous non-woven fabric with a porosity of 35% and a thickness of 7 μm, and the loading per unit area was 0.029 g / cm 2 , and covered with the same porous non-woven fabric again to form a sandwich structure, and embedded hot pressing was performed with a pressure of 300MPa and a heating temperature of 45°C. After hot pressing for 0.5h, an oxide-based membrane was obtained; the prepared gel electrolysis precursor solution was dip-coated on the surface of the oxide-based membrane, and in-situ polymerization was carried out at 25°C for 24h to obtain a composite gel electrolyte membrane with a membrane thickness of 19μm.

[0069] Comparative Example 2

[0070] Under inert gas conditions, 3.4g of 1,3-dioxolane, 1.2g of 1-ethyl-3-methylimidazolium tetrafluoroborate and 0.95g of lithium trifluoromethylsulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate were dissolved in 1.5g of fluoroethylene carbonate, wherein the mass ratio of lithium trifluoromethylsulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate was 6:3:1, and the mixture was stirred for reaction for 2h under a certain mechanical strength to obtain a gel electrolyte precursor solution; a porous non-woven fabric with a thickness of 7μm was coated on the surface and the same porous non-woven fabric was covered again to form a sandwich structure, and embedded hot pressing was performed at a pressure of 300MPa and a heating temperature of 45°C. After hot pressing for 0.5h, an oxide base film was obtained; the prepared gel electrolyte precursor solution was dip-coated on the surface of the oxide base film, and in-situ polymerized for 24h at 25°C to obtain a composite gel electrolyte membrane with a membrane thickness of 18μm.

[0071] Except that the slurry does not contain oxide but only contains polymer matrix, the rest of the contents are the same as those in Example 1 to obtain a composite gel electrolyte membrane.

[0072] Comparative Example 3

[0073] Under inert gas conditions, 3.4 g of 1,3-dioxolane, 1.2 g of 1-ethyl-3-methylimidazolium tetrafluoroborate, 1.8 g of lithium lanthanum zirconium oxide powder with a particle size of 300 nm and 0.95 g of lithium trifluoromethylsulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate were dissolved in 1.5 g of fluoroethylene carbonate, wherein the mass ratio of lithium trifluoromethylsulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate was 6:3:1. The reaction was stirred for 2 h under a certain mechanical strength to obtain a gel electrolyte precursor solution, and in situ polymerization was carried out at 25 ° C for 24 h to obtain a composite gel electrolyte membrane.

[0074] Test Case

[0075] The composite gel electrolyte membranes prepared in the above-mentioned Examples 1 to 10 and Comparative Examples 1 to 3 were subjected to impedance analysis tests, and the thickness of the bottom was calculated to obtain the ionic conductivity value of the electrolyte. The specific test process is as follows: the composite gel electrolyte membrane is assembled into a Swagelok battery, pressurized, and in-situ cured. After that, an AC impedance spectrum test is performed by an electrochemical workstation at room temperature, and the ionic conductivity of the composite gel electrolyte is calculated according to the impedance value; a solid-state button battery is assembled with a ternary positive electrode material, a lithium metal negative electrode, and a composite gel electrolyte membrane, and a charge and discharge test is performed at room temperature (25°C) and 0.5C; a Li / / Li symmetric battery is assembled for a lithium deposition stripping test, and the current density is set to 0.2mA / cm 2 The lithium deposition stripping time was set to 1 h and the lithium deposition stripping amount was 0.2 mAh / cm 2 , the verification test results are shown in Table 1:

[0076] Table 1

[0077]

[0078] As shown in Table 1, the button cell test data results show that within the appropriate range of raw material addition, the composite gel electrolyte membrane material ratio in Example 1 shows the highest ion conductivity, and the battery has a high capacity retention rate after 100 cycles at room temperature under high rate conditions, and the electrolyte has good stability to the lithium negative electrode. Combined with Comparative Examples 1-3, it is once again proved that ionic liquids and oxides help to form a through ion transfer mechanism, improve the lithium ion conductivity of the composite gel electrolyte membrane, and widen the potential window. The oxide-based membrane prepared by a simple embedded hot pressing process enhances the mechanical strength of the membrane and achieves a de-diaphragm effect. The modification and infiltration of the ionic liquid make the inorganic-organic layer completely composited, and the electrolyte membrane has good contact with the positive and negative electrode interfaces. The constructed composite gel electrolyte membrane structure system is more suitable for lithium metal solid-state batteries with ternary positive electrode systems.

[0079] Embodiment 11

[0080] A method for preparing a composite gel electrolyte membrane by in-situ polymerization, comprising the following steps:

[0081] Under inert gas conditions, 6.5 g of 1,3-dioxolane, 0.1 g of N-methyl, propylpiperidinium bis(trifluoromethanesulfonyl imide) salt and 2 g of lithium trifluoromethanesulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate were dissolved in 1.49 g of propylene carbonate, wherein the mass ratio of lithium trifluoromethanesulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate was 6:3:1. The reaction was stirred for 2 h under a certain mechanical strength to obtain a gel electrolyte precursor solution; 5 g of lithium germanium aluminum phosphate powder with a particle size of 10 μm was dispersed through a high-dispersion sieve onto the surface of a porous non-woven fabric with a porosity of 70% and a thickness of 50 μm, and the loading per unit area was 0.1 g / cm 2 , and covered with the same porous non-woven fabric again to form a sandwich structure, and embedded hot pressing was performed with a pressure of 500MPa and a heating temperature of 200°C. After hot pressing for 0.1h, an oxide-based membrane was obtained; the prepared gel electrolyte precursor solution was dip-coated on the surface of the oxide-based membrane, and in-situ polymerization was carried out at 80°C for 1h to obtain a composite gel electrolyte membrane with a membrane thickness of 130μm.

[0082] Example 12

[0083] A method for preparing a composite gel electrolyte membrane by in-situ polymerization, comprising the following steps:

[0084] Under inert gas conditions, 0.5 g of dimethyldioxirane, 2.3 g of N-methyl, propylpiperidinium bis(trifluoromethanesulfonyl imide) and 1.7 g of lithium trifluoromethanesulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate were dissolved in 5.5 g of fluoroethylene carbonate, wherein the mass ratio of lithium trifluoromethanesulfonyl imide, lithium tetrafluoroborate and lithium hexafluorophosphate was 6:3:1. The reaction was stirred for 2 h under a certain mechanical strength to obtain a gel electrolyte precursor solution. 0.5 g of lithium lanthanum titanium oxide powder with a particle size of 200 nm was dispersed through a high-dispersion screen onto the surface of a porous diaphragm with a porosity of 5% and a thickness of 2 μm, and the loading per unit area was 0.005 g / cm 2 , and then covered with the same porous diaphragm again to form a sandwich structure, and then embedded hot pressing was performed with a pressure of 20 MPa and a heating temperature of 100°C. After hot pressing for 6 hours, an oxide-based membrane was obtained; the prepared gel electrolyte precursor solution was dip-coated on the surface of the oxide-based membrane, and in-situ polymerization was carried out at 25°C for 160 hours to obtain a composite gel electrolyte membrane with a membrane thickness of 12 μm.

[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite gel electrolyte membrane, characterized in that: Here are the steps: (1) dissolving a polymer precursor, an ionic liquid and a composite lithium salt in an organic solvent to obtain a gel electrolyte precursor solution; (2) dispersing the inorganic oxide on the surface of the polymer matrix and hot pressing and compounding to obtain an oxide-based film; (3) coating the gel electrolyte precursor solution on the surface of the oxide base film and curing the solution to obtain a composite gel electrolyte membrane.

2. The method for preparing the composite gel electrolyte membrane according to claim 1, characterized in that: The mass proportion of each component in the gel electrolyte precursor solution is: polymer precursor 1-65%, ionic liquid 0.1-23%, composite lithium salt 1-20%, organic solvent 2-55%; the loading amount of inorganic oxide in the oxide base film is 0.005-0.1g / cm 2 .

3. The method for preparing the composite gel electrolyte membrane according to claim 2, characterized in that: The polymer precursor is at least one of 1,3-dioxolane, 1,4-dioxane, propylene oxide, tetrahydrofuran or dimethyldioxirane; the ionic liquid is at least one of imidazole ionic liquids, pyridine ionic liquids, pyrrolidine ionic liquids, quaternary amine ionic liquids, piperidine ionic liquids or quaternary phosphonium ionic liquids.

4. The method for preparing the composite gel electrolyte membrane according to claim 3, characterized in that: The composite lithium salt is at least one of lithium trifluoromethylsulfonyl imide, lithium trifluoromethylsulfonyl imide, lithium bis(oxalatoborate), lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium chloride, lithium hexafluorophosphate, lithium difluorooxalatoborate or lithium perchlorate; the organic solvent is at least one of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl formate, methyl acetate, N,N-dimethylacetamide, fluoroethylene carbonate, dimethyl ether, vinyl sulfite, propylene sulfite, tetrahydrofuran or hexamethylene diisocyanate.

5. The method for preparing the composite gel electrolyte membrane according to claim 4, characterized in that: The particle size of the inorganic oxide is 0.2-10 μm; the inorganic oxide is at least one of lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium titanium phosphate, lithium germanium aluminum phosphate, and lithium lanthanum titanium oxide.

6. The method for preparing the composite gel electrolyte membrane according to claim 1, characterized in that: The porosity of the polymer matrix is ​​5-70% and the thickness is 2-80 μm; the polymer matrix is ​​at least one of non-woven fabric, fiber membrane, melt-blown fabric, and porous diaphragm; the thickness of the oxide-based membrane is 10-65 μm.

7. The method for preparing the composite gel electrolyte membrane according to claim 6, characterized in that: The hot pressing composite is embedded hot pressing; the embedded hot pressing is one of single-sided dispersed internal pressure, double-sided dispersed internal pressure, and sandwich structure internal pressure, the pressure is 20-500MPa, the hot pressing temperature is 45-200°C, and the hot pressing time is 0.1-6h.

8. The method for preparing the composite gel electrolyte membrane according to claim 7, characterized in that: The coating method of the gel electrolyte precursor solution in step (3) includes at least one of spin coating, dip coating, spray coating, flat blade coating, and cast coating.

9. The method for preparing the composite gel electrolyte membrane according to claim 8, characterized in that: The curing treatment in (3) is in-situ thermal polymerization or in-situ photopolymerization; the polymerization curing temperature of the in-situ thermal polymerization is 25 to 80° C., and the time is 1 to 160 hours.

10. The composite gel electrolyte membrane prepared by the method according to any one of claims 1 to 9, characterized in that: The thickness of the composite gel electrolyte membrane is 12-130 μm.

Citation Information

Patent Citations

  • Flame-retardant composite electrolyte, manufacturing method and flame-retardant lithium battery

    CN117747922A

Cited By

  • Gel electrolyte, preparation method of gel electrolyte, battery and preparation method of battery

    CN120613443A